7D.10: EFFECTS OF MELATONIN ON CONTRACTILE RESPONSES IN SMALL ARTERIES OF AGEING MICE. (June 2015) - Rosei, C. Agabiti; De Ciuceis, C.; Rossini, C.; Porteri, E.; Rezzani, R.; Rodella, L.; Favero, G.; Sarkar, A.; Rosei, E. Agabiti; Rizzoni, D.
Abstract : Objective: It has been previously demonstrated that inflammation in adipose tissue may be implicated in vascular dysfunction (Circulation 2009; 119(12):1661–1670). A senescence-accelerated prone mouse (SAMP8) is a model of age-related cognitive decline and vascular dysfunction. Several studies demonstrated that SAMP8 suffers from increased oxidative stress and that accelerated senescence was associated with decreased eNOS and nNOS and increased oxygen radicals synthesis. Aim of the study was to investigate functional responses of small mesenteric arteries in a senescence-accelerated prone mouse (SAMP8) before and after chronic treatment with melatonin. Figure. No caption available. Design and method: We investigated 7 SAMP8 and 7 SAMR1 normal controls. Mesenteric small resistance arteries were dissected and mounted on a wire myograph, according to Mulvany-Halpern technique (internal diameter about 200 μm). A concentration-response to norepinephrine (NE, from 10–9 to 10-5 Mol/l) was evaluated in vessels with intact prerivascular fat tissue (WF) and in vessels in which perivascular fat tissue was removed (NoF). Investigations were repeated in 7 SAMP8 and 7 SAMR1 after 54 weeks of chronic treatment with melatonin, an endogenous hormone with antioxidant and vasculoprotective properties. Results: In SAMR1 control mice anticontractile effect of perivascular fat was present (WF vs. NoF: ANOVA p = 0.04), while in aging SAMP8 mice the effect was less pronounced (WF vs. NoF: ANOVA p = NS) (see figure). Long-term treatment with melatonin had no effect in SAMR1 either in WF or NoF vessels, while it decreased the contractile response to norepinephrine in noF vessels of SAMP8 (ANOVA p < 0.001); the effect of melatonin treatment in WF vessels was not statistically significant. Conclusions: The anticontractile effect of perivascular fat is impaired in a senescence-accelerated prone mouse, compared with controls. A long-term treatment with melatonin seems to decrease contractile responses to norepinephrine in NOF mesenteric small arteries of SAMP8, thus restoring an anticontractile effect, probably through antioxidant mechanisms.